Motivating employee ambidexterity: function and dysfunction of empowering leadership - Yin, Wenjun; Ouyang, Xi (Transformations In Business & Economics, 2026)
Drawing on the job demands–resources theory, this study aims to hypothesise and test the competing dual processes through which empowering leadership influences employee ambidexterity. In particular, the moderating role of task uncertainty in shaping the balance of empowering leadership’s effectiveness is explored. We used a time-lagged design to collect all variables in two phases. Of 475 employees, 389 usable responses from 83 innovative teams in central China were collected for analysis. The findings reveal that empowering leadership is positively associated with employees’ role control and role workload, which, in turn, have differential impacts on exploration activities: role control exerts a significantly positive influence, whereas role workload exerts a significantly negative influence. Conversely, while role control positively affects exploitation activities, role workload does not demonstrate a significant impact on exploitation. Moreover, task uncertainty moderates the relationship between empowering leadership and role control, weakening the positive association. These findings provide novel insights into the nuanced effects of empowering leadership on exploration and exploitation activities, offering practical implications for managers seeking to implement empowerment practices effectively.